1995
DOI: 10.1086/175489
|View full text |Cite
|
Sign up to set email alerts
|

Effect of adiabatic deceleration on the focused transport of solar cosmic rays

Abstract: In the framework of focused transport theory, adiabatic deceleration arises from adiabatic focusing in the solar wind frame and from differential solar wind convection. An explicit formula is given for the deceleration of individual particles as a function of the pitch angle. Deceleration and other first-order effects of the solar wind, including convection, are incorporated into a numerical code for simulating the transport of energetic particles along the interplanetary magnetic field. We use this code to mo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
187
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 200 publications
(190 citation statements)
references
References 22 publications
2
187
0
1
Order By: Relevance
“…In all the selected events, however, the inferred solar ion injections show a clear delay after the electron injections, even for ions and electrons with the same velocity. If solar energetic ions suffer energy loss due to adiabatic cooling during propagation in the IPM (Ruffolo 1995;Kocharov et al 1998), they would have traveled faster than that the observed ion energies indicate, and their solar release would become even later. Hence, in these events, the derived particle injections likely reflect the solar acceleration of low-energy electrons, of high-energy electrons, and of ions that occur at different times.…”
Section: Summary and Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…In all the selected events, however, the inferred solar ion injections show a clear delay after the electron injections, even for ions and electrons with the same velocity. If solar energetic ions suffer energy loss due to adiabatic cooling during propagation in the IPM (Ruffolo 1995;Kocharov et al 1998), they would have traveled faster than that the observed ion energies indicate, and their solar release would become even later. Hence, in these events, the derived particle injections likely reflect the solar acceleration of low-energy electrons, of high-energy electrons, and of ions that occur at different times.…”
Section: Summary and Discussionmentioning
confidence: 94%
“…3a), although these ions and electrons have the same velocity (∼0.060c). If ions suffer energy loss due to adiabatic cooling during their propagation in the IPM, they would have traveled faster than that the observed ion energy indicates and thus, their release at the Sun would have been even later (Ruffolo 1995;Kocharov et al 1998).…”
Section: Observationsmentioning
confidence: 92%
“…The transport model solves the focused transport equation (Roelof, 1969;Ruffolo, 1995), including the effects of particle streaming along the magnetic field lines, adiabatic focusing by the diverging magnetic field (Roelof, 1969), interplanetary scattering by magnetic fluctuations frozen into the solar wind (Jokipii, 1966;Dröge, 2003), convection with scattering fluctuations, and adiabatic deceleration resulting from the interplay of scattering and focusing (Ruffolo, 1995;Kocharov et al, 1998). Intensities for the Sun (STEREO A orange-dotted, STEREO B gray-dotted) and Antisun (STEREO A orange-dashed, STEREO B gray-dashed) fields of view are also displayed for both spacecraft in these two panels.…”
Section: Modelingmentioning
confidence: 99%
“…We describe the propagation of protons from a solar event by numerically solving a Fokker-Planck equation of pitch-angle transport that includes the effects of interplanetary scattering, adiabatic deceleration and solar wind convection (Roelof 1969;Ruffolo 1995;Nutaro, Riyavong, & Ruffolo 2001). We are assuming transport along the mean magnetic field, as expected when there is good magnetic connection between the source and the observer.…”
Section: Injection Near the Sun: Precision Modelingmentioning
confidence: 99%